PENINGKATAN SUMBER DAYA APARATUR DESA NANGA TONGGOI KECAMATAN KAYAN HULU KABUPATEN SINTANG - Erwandi, Antonius (Universitas Kapuas Sintang, 2025)
Human resources, especially village officials, are an important indicator in assessing institutional work performance. Increasing village apparatus resources can be increased through various aspects of activities, namely education, training, work supervision. This research uses a qualitative approach with a descriptive analysis type of research. The results of this research are that increasing the quality of the resources of Nanga Tonggoi village officials has not been optimally carried out, especially from the aspect of formal education, where none of the village and BPD officials have graduated from bachelor's level, while from the training aspect it has been carried out according to the needs of the village government by attending every training from the district government and province. Supervision is carried out internally by the village head through coordination and evaluation meetings, external supervision by the BPD is carried out in order to provide recommendations for the results of supervision in improving village apparatus resources.